2023
DOI: 10.1371/journal.pmed.1004172
|View full text |Cite
|
Sign up to set email alerts
|

Risk of fracture in adults with type 2 diabetes in Sweden: A national cohort study

Abstract: Background Type 2 diabetes mellitus (T2DM) is considered a risk factor for fracture but the evidence regarding the impact of T2DM on fracture risk is conflicting. The objective of the study was to determine if patients with T2DM have increased fracture risk and if T2DM-related risk factors could be identified. Methods and findings In this national cohort study in Sweden, we investigated the risk of fracture in 580,127 T2DM patients, identified through the national diabetes register including from both primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…( 34 ) While this might not affect every T2DM patient, the authors postulate that 21 million individuals are affected by a risk factor profile contributing to increased fracture risk. ( 34 ) A longer diabetes duration signifies prolonged high glucose condition within the body, which affects osseos cellular activity, leading to low bone turnover in T2D, which can result in more highly mineralized bone tissue and absence of microcrack removal. Additionally, the longer the high glucose condition continues, the more AGEs can be formed and, thus, impair collagen properties within the bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…( 34 ) While this might not affect every T2DM patient, the authors postulate that 21 million individuals are affected by a risk factor profile contributing to increased fracture risk. ( 34 ) A longer diabetes duration signifies prolonged high glucose condition within the body, which affects osseos cellular activity, leading to low bone turnover in T2D, which can result in more highly mineralized bone tissue and absence of microcrack removal. Additionally, the longer the high glucose condition continues, the more AGEs can be formed and, thus, impair collagen properties within the bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining fractures at non-hip sites are even fewer. Fractures of the ribs, humerus and distal leg/ankle are more common in type 2 diabetes [11,12]. Wrist fractures may not be increased in type 2 diabetes [11,12], despite the findings of a meta-analysis [3], which could have been driven by one case-control study.…”
Section: Burden Of Skeletal Fragility In Diabetesmentioning
confidence: 93%
“…Fractures of the ribs, humerus and distal leg/ankle are more common in type 2 diabetes [11,12]. Wrist fractures may not be increased in type 2 diabetes [11,12], despite the findings of a meta-analysis [3], which could have been driven by one case-control study. The risk of vertebral fractures also appears to be elevated in individuals with type 2 diabetes [11,13], although some studies found no difference when compared with those without diabetes [2,3], particularly in men [14].…”
Section: Burden Of Skeletal Fragility In Diabetesmentioning
confidence: 93%
“…In a recent Swedish registry study, fracture risk was higher in patients who were on insulin treatment, with low physical activity, a body mass index (BMI) below 25 kg m À2 , and long-standing disease duration but lower in most (55%) individuals with T2D than in age-and sex-matched background population. (8) Other factors are also considered to increase fracture risk in T2D, including increased risk of falls, poor glycemic control, and diabetes complications, including MVD. (9) Clinical studies based on high-resolution peripheral quantitative computed tomography (HR-pQCT) scans have shown an increased cortical porosity in T2D, (10) which appears to be most pronounced in T2D patients with MVD.…”
Section: Introductionmentioning
confidence: 99%